1995
DOI: 10.1007/bf00286372
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and microbial evaluation of in-situ bioremediation of hydrocarbons in anoxic groundwater enriched with nutrients and nitrate

Abstract: In-situ bioremediation of benzene, toluene, ethylbenzene and the xylenes (BTEX) was carried out in an O2-poor (approx. 1 mg O2/l) fuel-contaminated aquifer. Extracted groundwater, enriched with ammonium polyphosphate (nutrients) and KNO3 (electron acceptor), was piped to an infiltration gallery over the contaminated site. Before, during and after infiltration, BTEX, nitrate and different populations of culturable bacteria were measured. BTEX declined by 78% in water from the monitoring well which was most cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…All these studies showed depletion of contaminants at different degrees. Barbaro et al (1992) as well as Schreiber and Bahr (2002) showed that benzene was recalcitrant under anaerobic conditions while Gersberg et al (1995) observed benzene degradation under denitrification, and under aerobic conditions. Thereafter, residual concentrations were too low to assess whether benzene could be degraded under nitrate reduction.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…All these studies showed depletion of contaminants at different degrees. Barbaro et al (1992) as well as Schreiber and Bahr (2002) showed that benzene was recalcitrant under anaerobic conditions while Gersberg et al (1995) observed benzene degradation under denitrification, and under aerobic conditions. Thereafter, residual concentrations were too low to assess whether benzene could be degraded under nitrate reduction.…”
Section: Introductionmentioning
confidence: 92%
“…Barbaro et al (1992) injected gasoline saturated groundwater, nitrate and bromide in two wells to assess biotransformation of benzene, toluene, ethylbenzene and xylenes (BTEX) under denitrifying conditions. Others; (Gersberg et al, 1995; used infiltration galleries to perfuse nitrate and nutrients to study BTEX biodegradation, while Schreiber and Bahr (2002) injected tracers in wells as pulses under natural-gradient conditions. One of the longest EA injection was studied by Hunkeler et al (2002): aerated groundwater supplemented with nitrate and phosphate was injected for 4.5 years in an infiltration gallery to stimulate Diesel-fuel degrading microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…The wastewater treatment plant sludge from chemical industries is likely to contain indigenous microbial species that are acclimatized to a wide variety of contaminants. The most routine procedure for understanding the biodegradation and removal kinetics of BTEX compounds is to use mixed/pure cultures in batch and continuous systems (Alvarez and Vogel 1991;Gersberg et al 1995;Gusmão et al 2006). For instance, in batch system, the degradation of B, T and p-X individually and in mixtures by a mixed consortium and a Pseudomonas species showed benzene and toluene degradation but not p-xylene as individual substrates.…”
Section: Introductionmentioning
confidence: 98%
“…A classical strategy of in‐situ remediation injects treatment solutions into the polluted aquifer and facilitates the degradation of contaminants by bioremediation (e.g., Devlin et al., 2004; Domenico & Schwartz, 1998). For instance, the treatment solution, which contains oxidants and nutrients, is usually released to react with contaminant plumes of benzene, toluene, ethylbenzene, and xylenes (e.g., Barbaro et al., 1992; Chapman et al., 1997; Gersberg et al., 1995). The prerequisite for reaction between the injected solutions and the contaminant plumes is mixing, which is generally not sufficient in a groundwater system due to the slow water flow velocity (Fetter, 2000) and its resulting small dispersion coefficient (Bear, 1972).…”
Section: Introductionmentioning
confidence: 99%